Imagineering Mobility: Constructing Utopias for Future Urban Transport. (January 2014) - Timms, Paul; Tight, Miles; Watling, David
Over the past fifty years a growing body of work has sought to address the problem of planning for transportation in the long-term future through scenario building. Such thinking has generally been restricted to issues concerned with environmental sustainability and the 'images' of future transport so created are usually weak in terms of their social sustainability content, either treating social issues superficially, or ignoring them entirely, or even creating images that are socially undesirable. At the same time, there has generally been a marked decrease over the past twenty years in socially oriented Utopian thinking. As a direct result of these two factors, hardly any consideration has been given recently to imagining socially sustainable views of transport in a future utopia. The key underlying aim of this paper is to provide some background thinking about how this lack might be addressed. To do so, it examines concepts about utopia in terms of their form, content, and function, and considers possible reasons for the recent decline in Utopian thinking and their 'replacement' by a type of futures-thinking that is referred to as dystopian avoidance . It then examines transport characteristics of Utopian thinking in urban planning in the 20th century and considers various 'antinomies of transport' with respect to future Utopias. Based upon the insights gained, the paper comments on two existing 'practical' sets of transport-related scenarios in terms of their Utopian and dystopian characteristics. One particular result is that the Utopian aspects of these scenario sets in terms of their social content are relatively weak, in line with the hypothesised recent general decline in (social) Utopian thinking. Various conclusions are made which emphasise the usefulness of Utopian thinking in transport planning, particularly in participatory approaches. It is suggested that three elements of the transport system should be separately 'utopianised': The mobility of people and goods; physical aspects that facilitate or inhibit such mobility; and the system of governance with respect to formulating and implementing transport policy.